SE OF ARTIFICIAL INTELLIGENCE AND PROCEDURAL GUARANTEES: A CONSTITUTIONAL ANALYSIS OF DIGITAL ADVERSARIAL PROCEEDINGS (REMUNOM, 2026)
The incorporation of artificial intelligence into judicial proceedings has significantly transformed the administration of justice, particularly regarding efficiency and procedural speed. In this context, this study aims to analyze the use of artificial intelligence in judicial processes, focusing on its constitutional limits, especially in relation to procedural guarantees. This research is qualitative in nature, with an exploratory and descriptive approach, developed through a literature review based on recent scientific articles addressing the topic from legal and technological perspectives. The results indicate that, although artificial intelligence contributes to optimizing auxiliary activities within the judiciary, its use presents relevant risks, such as algorithmic opacity, the potential reproduction of biases, and the impairment of adversarial proceedings and the reasoning of judicial decisions. It was also found that automation cannot extend to the core of judicial decision-making, making human oversight and adherence to constitutional principles essential. It is concluded that the use of artificial intelligence in judicial processes must be limited and regulated to ensure compatibility with due process of law and the protection of fundamental rights.